1996
DOI: 10.1007/bf01855012
|View full text |Cite
|
Sign up to set email alerts
|

AR4-2J cells: A model to study polypeptide hormone receptors

Abstract: The AR4-2J cell line is derived from a transplantable tumour of the exocrine rat pancreas. Acinar in origin, this cell line contains significant amounts of amylase and can be grown in continuous culture. Many in vitro studies have been done using these cells; these studies were often complemented with in vivo experiments on animals. Particularly, many polypeptide hormones interacting with specific receptors located on the cell membrane have been analysed. The accurate knowledge of the hormone-receptor interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…The cell line retains many of the characteristics of pancreatic acinar cells in its differentiated state and is a general model to study stimulus-secretion coupling [13]. Stimulation of AR4-2J cells with different alcoholic beverages and appropriate ethanol solutions have shown that increasing beer dose increases amylase release, whereas pure ethanol, wine or alcoholic beverages produced by distillation (e.g., whisky, tequila) have no effect (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…The cell line retains many of the characteristics of pancreatic acinar cells in its differentiated state and is a general model to study stimulus-secretion coupling [13]. Stimulation of AR4-2J cells with different alcoholic beverages and appropriate ethanol solutions have shown that increasing beer dose increases amylase release, whereas pure ethanol, wine or alcoholic beverages produced by distillation (e.g., whisky, tequila) have no effect (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…It can be grown in continuous culture or maintained in vivo in athymic nude mice, SCID mice or in Lewis rats. This cell line is particularly attractive for in vitro receptor assays as it is known to express a variety of hormone receptors including cholecystokinin (CCK), epidermal growth factor (EGF), pituitary adenylate cyclase activating peptide (PACAP), somatostatin (sst2) and 12 Inthis model, male Lewis rats were implanted with solid tumor material in a similar manner as described for the CA20948 rat model. Palpable masses were present 7 days post implant and imaging studies were conducted on animals at 10-12 days post implant when the mass had achieved 2-2.5 g. This tumor line has been maintained in vivo for more than 30 generations without change in receptor expression.…”
Section: Pancreatic Acinar Carcinoma (Ar42-j) Tumormentioning
confidence: 99%
“…123 It has been used for many years as a model for studies of pancreatic acinar cell biology. 124,125 AR42J cells have been known to have some properties of endocrine cells, including the ability to express and store properly processed pancreatic polypeptide in secretory granules. 126 More recently, it has been shown that the combination of activin A and betacellulin 33 or HGF/SF 127 can induce approximately 10% of AR42J cells to express insulin.…”
Section: Radiation and Carcinogen-induced Rodent Pancreatic Endocrinementioning
confidence: 99%